Evaluation of employee sanitation and hygiene in the production of javanese noodles - Primayandi, Reiza; Khairi, Amalya Nurul (Journal of Halal Science and Research, 2022)
Evaluation of Industrial Sanitation and Employee Hygiene in Javanese Noodles Production. In the food industry, sanitation and hygiene are essential things in a food product or food safety from external contaminants or microbes that can affect the final product of the food production. The method of analysis used is the method of observation, interviews, direct practice, documentation, and library research. Check sheet based on CPPB-IRT reference Regulation of the Head of the Drug and Food Control Agency of the Republic of Indonesia Number HK.03.1.23.04.12.2206 of 2012 and the Food and Drug Monitoring Agency of 2020. This practical work report aims to determine the evaluation and application of industrial sanitation principles and employee hygiene and the efforts that can be made to improve industrial sanitation and employee hygiene. For things to be further evaluated, such as window construction or air ventilation. Steps that can be made to improve sanitation and hygiene for employees in the production of Javanese Noodles are to increase employee awareness of the importance of implementing sanitation and hygiene. This aims to minimize contamination of product production. It resulted from. From the results of direct observation and with a check sheet, it has been carried out according to the BPOM RI CPPB-IRT policy regulations.